USE OF AUGMENTED REALITY TO FOSTER REALISTIC INTERACTIONS IN THE BANKING SECTOR - Kumar, Parveen; Kohli, Deepika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The banking industry is undergoing rapid transformation, much of which has been driven by customer-facing technologies. This commentary provides an in-depth analysis of the adoption of AR is affecting the financial sector, focusing on its main influence on realistic client interactions. As a result, an AR-based approach could offer a solution to enhance the customer experience. AR technology has reached a level of maturity where the banking sector can effectively leverage it to deliver services, particularly by providing a more realistic and immersive experience for customers. Ultimately, we conclude that integrating AR into banking services promises to create a more dynamic and engaging experience, effectively bridging the gap between the physical and digital worlds.